DEVELOPMENT OF WATERSHED CARRYING CAPACITY AND SUSTAINABILITY INDEX (CASE STUDY: CIMAHI SUB WATERSHED) - RISANDRI HIKMAT, RAFID
Cimahi City is planned to become the center of Bandung Basin National Activity Center which is safe, comfortable, efficient, and sustainable as stated in Cimahi City Regional Regulation Number 4 of 2012 concerning the Cimahi City Spatial Plan for 2012-2032. The planning shows that many activities are carried out in Cimahi City such as from the domestic, agriculture, livestock, and industrial sectors so that can affect the decline of environmental quality, one of which is watershed. The Cimahi sub watershed is one of the five sub watersheds located in the area of Cimahi City and is part of the Citarum watershed. The sub watershed is included in the water resources network system development plan in the Cimahi City Regional Spatial Planning. In addition, because the Cimahi sub watershed is part of the Citarum watershed, it can be said that the sub watershed has contributed to pollution in the watershed.